Luke: An autonomous robot photographer - Zabarauskas, Manfredas; Cameron, Stephen (Proceedings - IEEE International Conference on Robotics and Automation, 2014)
An autonomous robot photographer should move around a crowd, avoiding collisions while taking reasonable pictures of the subjects within it. We present a system based on a low-cost Turtlebot platform, the Kinect sensor, and a consumer-grade stills camera, that fulfills this task while applying several rules of general photograph composition. The subsumption control system was built using the ROS platform, and novel software components include the crowd head detection, the photograph composition procedures, the subject-interface, and uploading the photographs to a social media website. The result is a system that shows good performance in a public environment, as evaluated by independent human judges; performing a statistical analysis of these results against other published work verified the quality of the resulting photographs.